PENGEMBANGAN MEDIA BULETIN MATEMATIKA BERBASIS PENDEKATAN REALISTIK PADA SISWA SEKOLAH DASAR - Ika Rachmawati; Supriyono Supriyono; Rintis Rizkia Pangestika (Fakultas Tarbiyah Universitas Ibrahimy, 2021)
The objectives of this study was to develop a mathematics bulletin media based on a realistic approach to fourth-grade elementary school students and its feasibility for use. The development model used in this research is the ADDIE (Analysis, Design, Development, Implementation, and Evaluation) development model. The data collection technique in this study was conducted by interviewing questioner, test, and documentation. The instruments used in this research was media expert validation sheets, material experts, and teacher practitioners, practicality sheets for students and learning mastery test questions. The results of the research on the development of mathematical newsletter media based on a realistic approach are: 1) this research produces products in the form of mathematical newsletter media based on a realistic approach for grade IV elementary school students, 2) the results of the feasibility analysis of newsletter media based on a realistic approach are obtained from validation by two expert lecturers and classroom teachers. IV elementary schools obtained a mean score of 3.58 with the valid category, the results of the practicality of the product were fulfilled from the student response questionnaire got a score of 98% with very positive criteria, and the product effectiveness test was fulfilled from the learning completeness test with learning completeness reaching 100%.